2017
DOI: 10.1007/s12649-017-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poultry Litter and Poultry Litter Biochar on Soil Microbial Respiration and Nitrifying Bacteria Activity

Abstract: treatment with mineral fertilisation applied (MF), by 59 and 77%, respectively. The significantly highest basal respiration value was determined in soil with 5 t DM ha −1 biochar. The application of poultry litter had significant effect on nitrifying bacteria activity (increase by 50%). Poultry litter biochar added to the soil in both doses contributed to an increase in nitrifying bacteria activity by 36 and 34%, respectively compared to MF treatment. Biochar had more adverse effect on soil microbial biomass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…On the other hand, Dempster et al [42], Zimmerman et al [18], and Mierzwa-Hersztek et al [20] observed a decrease in Cmic after the application of biochars. Dempster et al [42] suggested that reduced Cmic value after adding biochar to the soil may result from the presence of toxic substances in this material such as trace elements or polycyclic aromatic hydrocarbons (PAHs).…”
Section: Effect Of Sewage Sludge Biochars On Soil Microbial Activitymentioning
confidence: 96%
See 3 more Smart Citations
“…On the other hand, Dempster et al [42], Zimmerman et al [18], and Mierzwa-Hersztek et al [20] observed a decrease in Cmic after the application of biochars. Dempster et al [42] suggested that reduced Cmic value after adding biochar to the soil may result from the presence of toxic substances in this material such as trace elements or polycyclic aromatic hydrocarbons (PAHs).…”
Section: Effect Of Sewage Sludge Biochars On Soil Microbial Activitymentioning
confidence: 96%
“…The respiratory-activation quotient was established by dividing the basal respiration rate by the substrate-induced respiration rate according to International Organisation for Standardisation 17155 [37], and the metabolic quotient was determined as the ratio between microbial respiration and Cmic. It was expressed as a microgram of CO 2 ─C released per gram of biomass carbon per hour [20].…”
Section: Determination Of the Microbial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…A R 10 increase was found for heterotrophic respiration in different environments such as apple orchards [26] and the desert [47] after the application of biochar produced from wood and cotton straw, respectively. A significant increase in R 10 for total soil respiration was also observed in soils amended with poultry litter biochar [48].…”
Section: Discussionmentioning
confidence: 78%